Fatwas and Figures: How NU and Muhammadiyah Shape Religious Authority on Indonesian Instagram Accounts - Virga, Rika Lusri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Social media has significantly transformed how religious institutions communicate their teachings and assert authority among their followers. This shift became especially visible during the COVID-19 pandemic, when Islamic organizations in Indonesia were required to issue clear guidance on how to carry out religious practices at home. This study examines how the two largest Islamic organizations in Indonesia, Nahdlatul Ulama (NU) and Muhammadiyah, employed public figures and authoritative religious references such as fatwas in their digital communication strategies related to home-based worship. Drawing on Postill and Pink’s netnographic method, the research focused on the official Instagram accounts of the two organizations (@nuonline_id and @lensamu) over a four-month period from March to June 2020. Data were gathered through the observation of both visual and textual content, including captions, posts, and audience responses. The findings indicate that NU relied on respected religious figures and inter-institutional coalitions to legitimize its messaging, while Muhammadiyah emphasized structured authority through formal, systematic, and rationally composed official statements. The implication of this research is the potential to encourage religious institutions to utilize social media as a strategic arena for asserting authority, shaping public perceptions, and adapting their institutional roles in response to the evolving dynamics of society in the digital era. Media sosial telah membentuk ulang cara institusi agama dalam menyampaikan panduan keagamaan sekaligus menegaskan otoritasnya di hadapan para pengikutnya. Transformasi ini menjadi semakin jelas selama pandemi COVID-19, ketika organisasi Islam di Indonesia dituntut untuk memberikan arahan yang jelas terkait pelaksanaan ibadah di rumah. Penelitian ini bertujuan untuk mengkaji bagaimana dua organisasi Islam terbesar di Indonesia, yakni Nahdlatul Ulama (NU) dan Muhammadiyah dalam memanfaatkan figur publik dan rujukan otoritatif keagamaan (fatwa) di ruang digital, khususnya dengan pelaksanaan praktik ibadah di rumah. Penelitian dilakukan dengan metode netnografi dari Postill dan Pink terhadap akun Instagram resmi kedua organisasi tersebut (@nuonline_id dan @lensamu) selama empat bulan dari Maret hingga Juni 2020. Pengumpulan data dilakukan melalui observasi konten visual dan tekstual, meliputi caption, unggahan, dan respons publik di kedua akun Instagram tersebut. Temuan menunjukkan bahwa NU menggunakan tokoh-tokoh agama yang dihormati serta membangun koalisi kelembagaan yang luas untuk melegitimasi panduan-panduan yang disampaikan, sedangkan Muhammadiyah menekankan otoritas yang terstruktur melalui pernyataan resmi yang sistematis, formal, dan disusun secara rasional. Implikasi temuan ini dapat mendorong lembaga keagamaan untuk memanfaatkan media sosial sebagai arena strategis dalam menegaskan otoritas, membentuk persepsi publik, dan menyesuaikan peran institusional menghadapi dinamika masyarakat di era digital yang terus berkembang.